Hubungan Pengetahuan dan Dukungan Keluarga dengan Perilaku Pencegahan Stunting Pada Ibu Hamil di Puskesmas Jongaya Makassar - Qamariyah, Nur; N, Nursyamsiyah; Husna, Asmaul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Background: Stunting is a serious global health issue, particularly in developing countries. It occurs when children experience chronic nutritional deficiencies early in life, resulting in impaired physical growth and cognitive development. Stunting has long-term effects on health and quality of life. Objective: This study aims to analyze the relationship between pregnant women’s knowledge and family support with stunting prevention behavior at Jongaya Health Center, Makassar. Method: This cross-sectional quantitative study involved 42 pregnant women. Independent variables included maternal knowledge and family support, while the dependent variable was stunting prevention behavior. Correlation analysis was used to determine relationships among variables. Results: Most respondents had good knowledge (88.3%) and received strong family support (75.6%). Both factors were significantly associated with positive stunting prevention behavior. Pregnant women with higher knowledge and better family support exhibited better preventive practices. Conclusion: Maternal knowledge and family support are critical for stunting prevention. Nutritional education and active family involvement can enhance preventive behavior among pregnant women.